Pengaruh Media Scan Cards Augmented Reality terhadap Kecerdasan Naturalis Anak Usia 5-6 Tahun - Kania Aprilianti; Rita Kurnia; Enda Puspitasari (Journal on Education, 2023)
Based on field observations of the naturalist intelligence of children aged 5-6 years at PKS Housing PT. BPLP Enok District, Indragiri Hilir Regency still needs to be developed and optimized. The purpose of this study was to examine the effect of Augmented Reality Scan Cards on the naturalist intelligence of children aged 5-6 years. The study used an experimental method with a one group pre-test post-test design with a sample size of 15 children. The data collection technique used in this study was using observation sheets of naturalist intelligence in children. The data analysis technique used the t-test using the SPSS ver 20 program. From the results of data analysis, the tcount was 12.773 greater than ttable = 2.145 with sig 0.000 <0.05. It can be concluded that there are significant differences in naturalist intelligence in children before and after using Augmented Reality Scan Cards. Based on the results of hypothesis testing obtained there is an effect of Augmented Reality Scan Cards on the naturalist intelligence of children aged 5-6 years at PKS Housing PT. BPLP Enok District, Indragiri Hilir Regency, amounted to 57.82%.